1996
DOI: 10.1093/oxfordjournals.alcalc.a008160
|View full text |Cite
|
Sign up to set email alerts
|

An Open Multicentric Study Evaluating 4-Hydroxybutyric Acid Sodium Salt in the Medium-Term Treatment of 179 Alcohol Dependent Subjects

Abstract: We report the results of an "open' multicentre study evaluating the use, tolerability and therapeutic efficacy of the sodium salt of 4-hydroxybutyric acid (GHB) for the medium-term treatment of withdrawal symptoms in 179 patients with alcohol dependence followed up as outpatients. The follow-up of patients was 6 and 12 months after drug discontinuation. Following a daily oral administration of 50 mg/kg for approximately 6 months, no serious systemic or single-organ consequences leading to drug discontinuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 17 publications
(19 reference statements)
3
59
1
1
Order By: Relevance
“…In one study in opioid-dependent patients, 30 mg/kg (2.1 g/70 kg) GHB was found to significantly increase subjective ratings of 'good mood,' 'spaced,' 'sluggish,' and 'carefree' without significantly affecting psychomotor performance or ratings of 'liking' (Rosen et al, 1997). In an unblinded outpatient study that evaluated the ability of a larger dose of GHB (50 mg/kg or 3.5 g/70 kg tid) given three times daily for 24 weeks to promote abstinence from alcohol in alcoholdependent patients, approximately 10% of the patients increased the dose of GHB by 6-7 times the therapeutic dose to 300-350 mg/kg tid (21-24.5 g/70 kg tid), suggesting that GHB was reinforcing in this subset of alcoholic patients (Addolorato et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…In one study in opioid-dependent patients, 30 mg/kg (2.1 g/70 kg) GHB was found to significantly increase subjective ratings of 'good mood,' 'spaced,' 'sluggish,' and 'carefree' without significantly affecting psychomotor performance or ratings of 'liking' (Rosen et al, 1997). In an unblinded outpatient study that evaluated the ability of a larger dose of GHB (50 mg/kg or 3.5 g/70 kg tid) given three times daily for 24 weeks to promote abstinence from alcohol in alcoholdependent patients, approximately 10% of the patients increased the dose of GHB by 6-7 times the therapeutic dose to 300-350 mg/kg tid (21-24.5 g/70 kg tid), suggesting that GHB was reinforcing in this subset of alcoholic patients (Addolorato et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…A large multicenter trial with a parenteral application of bromocriptine showed that this substance did not reduce relapse rates [41]. GHB was effective in reducing relapses [2,3,13,19]. In a randomized, double-blind, double-dummy study, performed in our center, 50 mg/kg GHB reduced craving during withdrawal effectively.…”
Section: Da Agonists For Relapse Preventionmentioning
confidence: 93%
“…It is thought that sodium oxybate reacts like alcohol, reducing symptoms of craving and withdrawal (74). However, 30-40% of patients do not respond to GHB treatment (75).…”
Section: Other Pharmacotherapies Approved In the Countries Of The Eurmentioning
confidence: 99%